Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

please I want to show that $F_n(t)=P{(S_n\le t})=\int_0^tF_{n-1}(t-x)f(x)dx.$

My problem here is I do not have enough hypothesis to work with. What I only know is that $F(t)=\int_0^tf(s)ds$ and $F(t)*f(t)=\int_0^tF(t-x)f(x)dx$.

I think induction will help, but I am not sure. I need some hint.

share|cite|improve this question
What exactly is $S_n$? It seems to be the sum of $n$ independent random variables. Are these $n$ variables $n$ individual failure times with density function $f(s)$? And are you sure that $F_n(t)$ is a pdf which generally denotes a probability density function and not a cumulative probability distribution function which is often abbreviated as cdf or CDF? Your expression $F_n(t) = P(S_n \leq t)$ seems to indicate the latter. – Dilip Sarwate Oct 19 '11 at 16:18
Yes, $S_n $ is the sum of $n$ independent random variables known as the time of the $nth$ failure. The density function of $F_n(t)$ is $f_n(t)$ for each n. – Hassan Muhammad Oct 19 '11 at 16:30
"density function of $F_n(t)$"?? Are $f_1(t), f_2(t), \ldots, f_n(t)$ all the same function, e.g. $f_n(t) = \exp(-t), t > 0$ for all $n$, or are they different? And what about $f(x)$ appears in the first line of your question? Please revise your question to make it more easily understandable. – Dilip Sarwate Oct 19 '11 at 16:35
up vote 1 down vote accepted

If $S_n=X_1+\cdots+X_n$ with $(X_n)$ independent and $X_n$ with density $f_n$, then $$ \mathrm P(S_n\leqslant t\mid X_n=x)=\mathrm P(S_{n-1}\leqslant t-x\mid X_n=x)=\mathrm P(S_{n-1}\leqslant t-x)=F_{n-1}(t-x), $$ where the second equality stems from the fact that $S_{n-1}$ and $X_n$ are independent. Integrating this over $x$, one gets $$ F_n(t)=\mathrm P(S_n\leqslant t)=\int\mathrm P(S_n\leqslant t\mid X_n=x)\mathrm dP_{X_n}(x)=\int F_{n-1}(t-x)f_n(x)\mathrm dx. $$ In the case at hand $S_0=0$ and $S_1=X_1$ hence one can start the recursion at $F_0(t)=\mathbf 1(t>0)$ or at $F_1(t)=\mathrm P(X_1\leqslant t)=\int\limits_0^tf(x)\mathrm dx$. And all the $X_k$ are almost surely positive hence $f_n(x)=0$ for $x\leqslant0$ and $F_{n-1}(t-x)=0$ for every $x\geqslant t$, thus the integral giving $F_n(t)$ may be restricted to $0\leqslant x\leqslant t$.

More generally, if $W=U+V$ for independent random variables $U$ and $V$ and if $U$ has CDF $G$ defined by $G(t)=\mathrm P(U\leqslant t)$ and $V$ has density $h$, then the CDF of $W$ is $$ \mathrm P(W\leqslant t)=\int G(t-x)h(x)\mathrm dx. $$

share|cite|improve this answer
Thanks Didier, I am happy with your help. – Hassan Muhammad Oct 23 '11 at 21:48
Thanks. It is customary on the site to show one's appreciation of an answer by voting for it and, if one is the author of the question, by accepting the answer. – Did Oct 23 '11 at 22:57

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.